Combined system of automatic control of water level in drum of steam generators of nuclear power plants with water-water power reactor - G. T. Kulakov; S. M. Satcuk; A. N. Kuhorenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The structure forming method and dynamic configuration of combined system of automatic control of water level in drum of steam generators of nuclear power stations with water-water power reactor on the basis of the transfer functions of optimal controllers using the principles of the theory of invariance is given. Comparison of direct quality indicators of three automatic control systems (standard and three-shots, digital system with the state observer and proposed combined automatic control system) is realized. The simulation results of transients, when change of steam flow rate is 10 % and power unit load changes plannedly, have confirmed advantages of the proposed combined system.